Assessment of caregiver expectations of physician communication in a pediatric setting - Lee, Tyler (BMC Health Serv Res, 2020)
BACKGROUND: In pediatrics, communication often occurs through an intermediary such as a caregiver. The goal of this study is to assess caregiver communication expectations and determine if meeting expectations influences caregiver satisfaction or instruction retention. METHODS: A survey study was performed at the Children’s Hospital of Philadelphia. Before the visit, caregivers completed a survey on communication expectations, Caregiver Expected Kalamazoo Essential Elements Communication Checklist (Caregiver Expected KEECC). After the visit, caregivers were surveyed on their perception of physician communication (Caregiver Perceived KEECC) and satisfaction. Caregivers were contacted 1 week after the clinic visit to assess instruction retention. Meeting of caregiver expectation was calculated by the difference between Caregiver Expected and Caregiver Perceived KEECC scores. RESULTS: 112 caregivers participated in the study. There was no significant difference in Caregiver Expected KEECC versus Caregiver Perceived KEECC score (4.39 vs 4.56). Caregiver communication expectations were exceeded in 51.5% of the visits. Communication expectations were exceeded more among caregivers with at a college education (p <  0.01) and more among White caregivers (p <  0.01). The average caregiver satisfaction score with the clinic visit was 4.67. Higher satisfaction scores were observed in caregivers who had their communication expectations met or exceeded (p <  0.01). Caregivers with communication expectations exceeded had higher percentage recall of physician instructions (p <  0.01). CONCLUSIONS: Caregiver communication expectations may be influenced by demographic factors. Communication expectation affects visit outcomes including caregiver satisfaction and instruction retention. Therefore, physicians need to be cognizant of caregiver communication expectations, which can impact quality of the healthcare experience.